RETRACTED: The language of Uzbek films of the independence period in the mirror of morphological standards - Shirinova Mekhrigiyo; Rajabova Marifat; Amonova Zilola; Safarova Hilola; Qo’ldoshev Rustambek (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001